2015
DOI: 10.18632/oncotarget.5854
|View full text |Cite
|
Sign up to set email alerts
|

Senescent stromal cells induce cancer cell migration via inhibition of RhoA/ROCK/myosin-based cell contractility

Abstract: Cells induced into senescence exhibit a marked increase in the secretion of pro-inflammatory cytokines termed senescence-associated secretory phenotype (SASP). Here we report that SASP from senescent stromal fibroblasts promote spontaneous morphological changes accompanied by an aggressive migratory behavior in originally non-motile human breast cancer cells. This phenotypic switch is coordinated, in space and time, by a dramatic reorganization of the actin and microtubule filament networks, a discrete polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 38 publications
(50 reference statements)
2
48
0
Order By: Relevance
“…Interestingly, in this model, malignant cells induce the collective invasion of epithelial cells considered to not be invasive [61]. The transformation from noninvasive to invasive phenotype was also observed in cells exposed to senescence-associated secretory phenotype (SASP), which inhibits ROCK/RhoA and promotes migration [161].…”
Section: Collective Cell Migrationmentioning
confidence: 78%
“…Interestingly, in this model, malignant cells induce the collective invasion of epithelial cells considered to not be invasive [61]. The transformation from noninvasive to invasive phenotype was also observed in cells exposed to senescence-associated secretory phenotype (SASP), which inhibits ROCK/RhoA and promotes migration [161].…”
Section: Collective Cell Migrationmentioning
confidence: 78%
“…RhoA promotes focal adhesion and regulates cell contractility, leading to the cell migration [ 25 ]. Wnt3a triggers RhoA activity to regulate neurite retraction of mouse neuroblastoma cells [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that the SASP from senescent stromal fibroblasts inhibits the RhoA/ROCK/myosin-dependent cell contractility leading to aggressive cell motility in human breast cancer cells [48]. However, the exact key SASP factors and the mechanisms involved in cSCC cell migration have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%